A novel oral formulation of the melanocortin-1 receptor agonist PL8177 resolves inflammation in preclinical studies of inflammatory bowel disease and is gut restricted in rats, dogs, and humans - Dodd, John; Jordan, Robert; Makhlina, Marie; Barnett, Keith; Roffel, Ad; Spana, Carl; Obr, Alison; Dhingra, Priyanka; Kayne, Paul S. (Frontiers in Immunology, 2023)
PL8177 is a potent and selective agonist of the melanocortin 1 receptor (MC1R). PL8177 has shown efficacy in reversing intestinal inflammation in a cannulated rat ulcerative colitis model. To facilitate oral delivery, a novel, polymer-encapsulated formulation of PL8177 was developed. This formulation was tested in 2 rat ulcerative colitis models and evaluated for distribution, in vivo, in rats, dogs, and humans. The rat models of colitis were induced by treatment with 2,4-dinitrobenzenesulfonic acid or dextran sulfate sodium. Rats treated with 50 µg oral PL8177 demonstrated significantly lower macroscopic colon damage scores and improvement in colon weight, stool consistency, and fecal occult blood vs the vehicle without active drug. Histopathology analysis resulted in the maintenance of intact colon structure and barrier, reduced immune cell infiltration, and increased enterocytes with PL8177 treatment. Single nuclei RNA sequencing of colon tissues was performed to characterize the mechanism of action. Transcriptome data show that oral PL8177 50 µg treatment causes relative cell populations and key gene expressions levels to move closer to healthy controls. Compared with vehicle, treated colon samples show negative enrichment of immune marker genes and diverse-immune related pathways. The distribution and concentration of PL8177 and the main metabolite within the GI tract after a single oral dose of PL8177 was investigated in rats and dogs. A phase 0 clinical study using a single microdose (70 µg) of [14C]-labeled PL8177 investigated the release of PL8177 in the colon of healthy men after oral administration. In rats and dogs, orally administered PL8177 was detected at higher amounts in the colon vs upper GI tract. [14C]-PL8177 and the main metabolite were detected in the feces but not in the plasma and urine in humans. This suggests that the parent drug [14C]PL8177 was released from the polymer formulation and metabolized within the GI tract, where it would be expected to exert its effect. Collectively, these findings support further research into the oral formulation of PL8177 as a possible therapeutic for GI inflammatory diseases in humans.